(untitled) (Revista de Estudios Europeos, 2022)
This article begins with an analysis of the Common European Asylum System, specifically in the case of Spain, to address the paradigmatic position of the right to asylum as a protector of the right to life. It is analyzed in the following pages how asylum contributes to integrate the subject requesting protection within the juridical-legal and social structure of the host State, while the State is integrated into the International Community as an entity that respects Human Rights. In conclusion, asylum makes it possible to think of a particular global citizenship, without effective citizenship but built from the imperative of protecting human life, regardless of the State of belonging. From this perspective, the analysis of asylum shows a theoretical and socio-political background that underlines the current status of asylum not only in quantitative but also qualitative terms.